Study of the testis in the active and hibernating hedgehog - Machin, C; Arnanz, E (Folia morphologica, 1989)
The structure and ultrastructure of the hedgehog's testis has been studied during active and hibernating states. The maximum activity of the hedgehog's testis manifest itself in spring and summer. In autumn they enter in a seasonal resting, in which, the interstitial cells atrophy and it can observe primary spermatocytes resting next to spermatogonia and supporting cells in the seminiferous tubules. These have a minimal diameter and contain only primary spermatocytes in hibernating period also the seminiferous epithelium that compound the walls of the tubules are about 72 microns thick in the active period and about 47 microns in hibernation. The Sertoli cells shows a small diameter in hibernation than in the active season. The nucleus has one or two nucleoli with distinguish themselves from those observed in the active season because of their closer union with the inner nuclear envelope. In autumn (resting period) the interstitial tissue regress and the Leydig cells are aggregated in blocks with little cytoplasm, minimum size nuclei and 1 or 2 nucleolus closely to the inner nuclear membrane. Like then in the ovary, the hedgehog's testis follows a seasonal cycle determined by the temperature and environmental changes and it have a power of physiological adaptation inherent of a typical hibernating animal.
Keywords: Hedgehogs; Hibernation; Testis; ježkovití; mužské pohlaví; hibernace; zvířata; Animals; testis; Male